1983
DOI: 10.1139/m83-123
|View full text |Cite
|
Sign up to set email alerts
|

Observation of symbiote migration in human body lice with scanning and transmission electron microscopy

Abstract: Bacterial symbiotes in the human body louse Pediculus humanus migrate from the mycetome to the lateral oviducts during the adult molt. Their migration was first described by Ries (E. Ries. 1931. Z. Morphol. Oekol. Tiere, 20:233-367.), who examined sectioned specimens with light microscopy. The present study is a more detailed investigation which involves the use of scanning and transmission electron micrographs. The results of our studies confirm Ries' observations. Micrographs are presented of symbiotes emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 2 publications
2
30
0
Order By: Relevance
“…1). Hence, their symbiotic bacteria are likely of independent evolutionary origins, as reflected in the different types of a symbiotic organ, namely, the highly specialized organ called the stomach disk, in human lice (13,34,37) and the loosely associated bacteriocytes in C. columbae ( Fig. 3 and 4) (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Hence, their symbiotic bacteria are likely of independent evolutionary origins, as reflected in the different types of a symbiotic organ, namely, the highly specialized organ called the stomach disk, in human lice (13,34,37) and the loosely associated bacteriocytes in C. columbae ( Fig. 3 and 4) (34).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there are several peculiar features that are shared between the endosymbiotic systems of sucking lice and chewing lice, such as the symbiont migration to the ovary at the third instar and the specialized tissue formations for symbiont transmission called ovarial ampullae ( Fig. 3 and 4) (8,13,34,37). These shared features are perhaps indicative of some common developmental and evolutionary bases underlying their endosymbiotic systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the stomach disc, the signals showed radial compartmentlike structures (Fig. 1B), which had been described as the locations of the symbiotic bacteria (4,11,20). A three-dimensional FISH movie image of the stomach disc is available in the supplemental material.…”
mentioning
confidence: 97%
“…In the 1920s, human lice were first reported to possess a large aggregate of bacteriocytes, called the stomach disc, on the ventral side of the midgut, in which rod-shaped symbiotic bacteria are harbored (5,23). Since then, a number of histological (11,20), embryonic (4,20), experimental (1,2,3,10), and nutritional (18,19) studies have been conducted on the endosymbiotic system of human lice. These studies demonstrated that the symbiont is vertically transmitted from the maternal stomach disc to developing oocytes through a peculiar passage (11,20), is essential for the survival and growth of the host (3), and provides the host with B vitamins that are lacking in the blood meal (19).…”
mentioning
confidence: 99%
“…37 The bacteria are gram positive, with an unnamed species. 38 In the female of the species, all bacteria leave their intracellular location and migrate to the ovary after the final molt. 38,39 The symbiote migration occurs 20 days after lice have hatched from the egg.…”
Section: Symbiotic Bacteria In Head Licementioning
confidence: 99%